Avaliação dos efeitos da lei Kandir sobre a arrecadação de ICMS no Estado do Ceará - Leitão, Alejandro Magno Lima (2009)
The Complementary Law no. 87/96, known as Kandir Law, promoted significant changes in the Tax Movement of Goods and Services (ICMS), the exemption from the jurisdiction of this state tax on exports of primary products and semi-prepared. The measure of depreciation tax, imposed by the government through the Law, seeking to give the Brazilian product more competitive in the international market. Was offered to the states a "revenue insurance" as a compensation of possible losses in revenues. Lack of a wider reform in the Brazilian tax system has increased the competition between states and between them and the union by revenue sharing. The State of Ceará, despite the small relative share in total Brazilian exports, also bitter loss of revenue due to the immunity tax on sales to the external market. The estimated values show a lack of federal transfers in compensation for loss of revenues from ICMS to Ceará.